Tiny life - Schlesinger, Emily (Red rhino books. Nonfiction., 2020)
Presents the history of microbiology and what we have learned from it, and highlights the microscope, bioluminescence, water bears, and bacteria. Includes color photographs, a glossary, and fact boxes.